Modified Flipped Classroom to Increase Readiness, Engagement and Understanding of Midwifery Students in Basic Science Course - Lenny Oktorina; Yuni Nurchasanah; Yudi Feriandi (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Covid-19 pandemic has prompted an opportunity to use technology to help students understand difficult topics such as basic science. The flipped classroom method has been widely used to increase the students' active roles. This study aims to measure the impact of modified flipped classroom to the undergraduate midwifery student's readiness, engagement, and understanding. This study used an embedded experimental model with an uncontrolled one-group pre-post-test quasi-experimental design on a total sampling of 37 first-year undergraduate diploma midwifery education students. The treatments were exposure to pre-class physiology video teaching materials and the flipped classroom. Kirkpatrick levels 1 and 2 were used to measure satisfaction and learning using closed Likert scales and open-ended questionnaires. Students' pre and post-test scores were measured and analysed using paired t-tests. Open questionnaire answers were analysed using content analysis. The statistical result showed significance difference (p <0.0001) with an increase in the average pre-post test score of 49%. The qualitative data revealed that the modified flipped classroom could increase active learning, self-reflection, learning material mastery and repetition, student readiness, lecturing effectiveness, and learning pace equity. The modified flipped classroom method was effective to increase the readiness, engagement, and understanding of the midwifery students in basic science course. Suggestions for future researchers are to add additional variables in the study to measure the impact of modified flipped classroom, such as learning motivation, student satisfaction, and academic outcomes. This will provide a more comprehensive picture of the effects of using this method on learning outcomes and student experience. Keyword: Flipped classroom, Kirkpatrick, Midwifery, Online learning, Physiology